2002
DOI: 10.1046/j.1365-2958.2002.03169.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and analysis of the biosynthetic gene cluster for the azoxy antibiotic valanimycin

Abstract: SummaryStreptomyces viridifaciens MG456-hF10 produces the antibiotic valanimycin, a naturally occurring azoxy compound. Valanimycin is known to be derived from valine and serine with the intermediacy of isobutylamine and isobutylhydroxylamine, but little is known about the stages in the pathway leading to the formation of the azoxy group. In previous studies, a cosmid containing S. viridifaciens DNA was isolated that conferred valanimycin production upon Streptomyces lividans TK24. Subcloning of DNA from the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
91
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 52 publications
3
91
0
Order By: Relevance
“…This finding suggests that an additional SerRS gene might be present in S. viridifaciens. The presence of a second SerRS gene (svsR) in S. viridifaciens has been subsequently confirmed by PCR experiments (21). As expected, the translation product of svsR exhibited a high degree of identity (91%) to the SerRS of S. coelicolor but a relatively low level of identity to VlmL (39%).…”
supporting
confidence: 57%
See 4 more Smart Citations
“…This finding suggests that an additional SerRS gene might be present in S. viridifaciens. The presence of a second SerRS gene (svsR) in S. viridifaciens has been subsequently confirmed by PCR experiments (21). As expected, the translation product of svsR exhibited a high degree of identity (91%) to the SerRS of S. coelicolor but a relatively low level of identity to VlmL (39%).…”
supporting
confidence: 57%
“…Previous investigations have shown that the valanimycin producer S. viridifaciens contains two genes that appear to code for SerRSs (21). Sequence analysis suggests that one of these genes (svsR) is likely to play a primary metabolic role, whereas the second gene (vlmL), which is embedded in the valanimycin gene cluster, appears to be involved in valanimycin biosynthesis (21).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations